Physical vapor deposition synthesis of two-dimensional orthorhombic SnS flakes with strong angle/temperature-dependent Raman responses. Issue 4 (24th December 2015) - Xia, Jing; Li, Xuan-Ze; Huang, Xing; Mao, Nannan; Zhu, Dan-Dan; Wang, Lei; Xu, Hua; Meng, Xiang-Min
Abstract : We synthesize 2D orthorhombic SnS flakes on a large scale and demonstrate their marked angle/temperature-dependent Raman response. Abstract : Anisotropic layered semiconductors have attracted significant interest due to the huge possibility of bringing new functionalities to thermoelectric, electronic and optoelectronic devices. Currently, most reports on anisotropy have concentrated on black phosphorus and ReS2, less effort has been contributed to other layered materials. In this work, two-dimensional (2D) orthorhombic SnS flakes on a large scale have been successfully synthesized via a simple physical vapor deposition method. Angle-dependent Raman spectroscopy indicated that the orthorhombic SnS flakes possess a strong anisotropic Raman response. Under a parallel-polarization configuration, the peak intensity of Ag (190.7 cm −1 ) Raman mode reaches the maximum when incident light polarization is parallel to the armchair direction of the 2D SnS flakes, which strongly suggests that the Ag (190.7 cm −1 ) mode can be used to determine the crystallographic orientation of the 2D SnS. In addition, temperature-dependent Raman characterization confirmed that the 2D SnS flakes have a higher sensitivity to temperature than graphene, MoS2 and black phosphorus. These results are useful for the future studies of the optical and thermal properties of 2D orthorhombic SnS.